2019
DOI: 10.1002/cpdd.749
|View full text |Cite
|
Sign up to set email alerts
|

A Thorough QT Study to Evaluate the Effects of a Supratherapeutic Dose of Sertraline on Cardiac Repolarization in Healthy Subjects

Abstract: The effect of steady‐state supratherapeutic sertraline (Zoloft) on QT interval was assessed in a single‐center, randomized, 3‐way crossover, double‐blind, placebo‐ and moxifloxacin‐controlled thorough QT study. Healthy adults received sertraline 400 mg/day, moxifloxacin 400 mg, and placebo, with a washout period (≥14 days) between treatments. A 12‐lead electrocardiogram was recorded in triplicate before dosing and at selected time points up to 72 hours after dosing. Analysis of covariance using a mixed‐effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Most of the information analyzed in this review was obtained from retrospective studies [52, 70-72, 80, 126]. Prospective studies [74], especially consistent with level A evidence [102], have been sporadic. Studies rarely analyzed risk factors for QTc and TdP prolongation, such as age, gender, cardiovascular disease, and concomitant therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the information analyzed in this review was obtained from retrospective studies [52, 70-72, 80, 126]. Prospective studies [74], especially consistent with level A evidence [102], have been sporadic. Studies rarely analyzed risk factors for QTc and TdP prolongation, such as age, gender, cardiovascular disease, and concomitant therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In 4 of 9 studies, sertralineinduced prolongation of the QTc interval was not found [96][97][98]101]. However, 5 studies have demonstrated QTc prolongation from borderline values with therapeutic doses [44,78], which occur rarely [77], to a significant prolongation of the QTc interval with sertraline at toxic doses [102]. The latest study was conducted by the manufacturer and is grade A evidence [102].…”
Section: Tetracyclic Antidepressantsmentioning
confidence: 99%
See 1 more Smart Citation
“…across multiple domains, such as electrochemical domain for design of lithium ion batteries [4], in solar cells [5] and many other fields, proteresis too is a phenomenon observed in the magnetic topology of a dirac cone [6], the magnetic loop of a mixed spin Ising system [7] and in anti-ferromagnetic alloys [8,9]. It is also observed in nanoparticles like Cu 2 O/CuO and cobalt [10,11], polycrystalline-silicon thin-film transistors [12] and in different kinds of drugs used for pharmacokinetics and pharmacodynamics [13,14]. A reference model is studied for piezoelectric micro-positioning platform for high precision tracking and positioning applications [15].…”
Section: Introductionmentioning
confidence: 99%